2014
DOI: 10.1039/c4ta01235f
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical CNT@NiCo2O4core–shell hybrid nanostructure for high-performance supercapacitors

Abstract: Ultrathin NiCo2O4 nanosheets directly grown on one-dimensional CNTs, as high-performance electrode materials for supercapacitors, were synthesized through a facile chemical co-deposition process combined with post-calcination in air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(47 citation statements)
references
References 40 publications
2
44
1
Order By: Relevance
“…It was observed that 69.9% of the capacitance could be retained when the current density was increased 10 times, showing good rate capability of the asymmetric supercapacitor. It should be noted that the areal specific capacitance and rate performance of complete supercapacitor are not as excellent as the single 3D porous NiCo 2 O 4 /Ni electrode tested in three-electrode cell, which is similar to the previous reports [39,40]. It might be attributed to the separator and the another electrode as well as the complete supercapacitor fabrication process.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…It was observed that 69.9% of the capacitance could be retained when the current density was increased 10 times, showing good rate capability of the asymmetric supercapacitor. It should be noted that the areal specific capacitance and rate performance of complete supercapacitor are not as excellent as the single 3D porous NiCo 2 O 4 /Ni electrode tested in three-electrode cell, which is similar to the previous reports [39,40]. It might be attributed to the separator and the another electrode as well as the complete supercapacitor fabrication process.…”
Section: Resultssupporting
confidence: 55%
“…For example, NiCo 2 O 4 nanosheets, nanoneedle, wires arrays grown on Ni foam exhibit greatly improved electrochemical performance with very high capacitance and excellent cycling stability [23,25e27]. NiCo 2 O 4 nanosheets also demonstrate very good capacitive performance by coating on carbon nanotubes or carbon nanofibers [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…20-0781). 4 It is worth mentioning that the pattern shows a weak crystalline state and no other peaks are observed, which effectively confirms the purity of the obtained NiCo 2 O 4 phase. Figure 2 shows CVs of the zinc metal and the obtained NiCo 2 O 4 at a scan rate of 2 mV s -1 in a mixed Li(OH)/ KOH aqueous electrolyte.…”
Section: Resultssupporting
confidence: 66%
“…In the past years, several approaches have been developed to overcome these issues. Constructing the composites of conducting additive (carbon-based materials [32][33][34], metal nanoparticles [18,35], etc.) and NiCo 2 O 4 , has been employed to achieve high-performance hybrid electrodes with high conductivity and large energy density.…”
mentioning
confidence: 99%